Murine Renal Transcriptome Profiles Upon Leptospiral Infection: Implications for Chronic Kidney Diseases. (2nd June 2018) - Chou, Li-Fang; Chen, Ting-Wen; Yang, Huang-Yu; Chang, Ming-Yang; Hsu, Shen-Hsing; Tsai, Chung-Ying; Ko, Yi-Ching; Huang, Chiung-Tseng; Tian, Ya-Chung; Hung, Cheng-Chieh; Yang, Chih-Wei
Abstract: Background: Leptospirosis caused by pathogenic Leptospira spp leads to kidney damage that may progress to chronic kidney disease. However, how leptospiral infections induced renal damage is unclear. Methods: We apply microarray and next-generation sequencing technologies to investigate the first murine transcriptome-wide, leptospires-mediated changes in renal gene expression to identify biological pathways associated with kidney damage. Results: Leptospiral genes were detected in renal transcriptomes of mice infected with Leptospira interrogans at day 28 postinfection, suggesting colonization of leptospires within the kidney with propensity of chronicity. Comparative differential gene expression and pathway analysis were investigated in renal transcriptomes of mice infected with pathogens and nonpathogens. Pathways analysis showed that Toll-like receptor signaling, complements activation, T-helper 1 type immune response, and T cell-mediated immunity/chemotaxis/proliferation were strongly associated with progressive tubulointerstitial damage caused by pathogenic leptospiral infection. In addition, 26 genes related with complement system, immune function, and cell-cell interactions were found to be significantly up-regulated in the L interrogans -infected renal transcriptome. Conclusions: Our results provided comprehensive knowledge regarding the host transcriptional response to leptospiral infection in murine kidneys, particularly the involvement of cell-to-cell interaction in the immune response. It would provide valuable resources to explore functional studies of chronic renal damage caused by leptospiral infection. Abstract : Leptospirosis caused by Leptospira spp. leads to kidney damage that may progress to chronic kidney disease. We profiled the renal transcriptome of C57BL/6 mice for chronic infection by leptospires and discuss the molecular mechanisms underlying the Leptospira-mediated renal dysfunction.